Phronetic leadership style evaluation with a fuzzy logic application - Vanharanta Hannu; Einolander Jarno; Kantola Jussi; Markopoulos Evangelos; Sivula Ari (TAYLOR & FRANCIS LTD, 2022)
The purpose of leadership style assessments is to determine the basic features and characteristics of leadership behaviours and to reveal the leader's personality traits and abilities and to increase their self-awareness. The style can be, for example, democratic, autocratic, bureaucratic, laissez-faire, strategic, visionary, transformational, or transactional. However, ordinary assessments do not help leaders analyze their knowledge and wisdom behind their behaviours. The Wisdom Cube seeks to explain wisdom through the four dimensions of wisdom and provides a practical way of understanding the knowledge and wisdom in leadership. By utilising the dimensions and planes of the Wisdom Cube, we can find the way from data handling, information processing, and knowledge creation to wisdom generation. The aim of this research is, therefore, to reveal the ontology of the phronetic leader and to create a practical evaluation tool for leaders. The content of the article covers the elements of the Wisdom Cube, presents related efforts to measure and analyze phronetic leadership characteristics, and shows the practical results of the first test runs with the fuzzy logic-based application. The personal deep understanding of the leadership traits may then help the leaders to turn their current leadership styles more phronetic.